2022
DOI: 10.1177/01945998221096593
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Services Provided to Medicare Beneficiaries by Otolaryngologists in 2020

Abstract: Telemedicine utilization among otolaryngologists was rare prior to the COVID-19 pandemic. We sought to understand rates of telemedicine utilization by otolaryngologists amid unprecedented changes in care delivery during the pandemic. Using Medicare Physician/Supplier Procedure Summary data, we performed a retrospective cross-sectional analysis of telemedicine services provided to Medicare beneficiaries by otolaryngologists in 2020. The total number of services and amount of reimbursement received by otolaryngo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Telemedicine use in otolaryngology increased substantially in response to the COVID-19 pandemic. 1 Prior literature at 1 institution noted found that patient participation with telemedicine at the peak of the pandemic, from March to May 2020, was associated with demographics such as age, sex, insurance, marital status, and income. 10 Specifically, patients who identified as male, were older in age, and had a lower median household income were less likely to use virtual care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telemedicine use in otolaryngology increased substantially in response to the COVID-19 pandemic. 1 Prior literature at 1 institution noted found that patient participation with telemedicine at the peak of the pandemic, from March to May 2020, was associated with demographics such as age, sex, insurance, marital status, and income. 10 Specifically, patients who identified as male, were older in age, and had a lower median household income were less likely to use virtual care.…”
Section: Discussionmentioning
confidence: 99%
“…In the wake of the COVID-19 pandemic, otolaryngologists significantly increased the delivery of telemedicine services to support patient access to care while preventing illness transmission. [1][2][3] Studies in multiple specialties have demonstrated that despite expansion of telehealth, marginalized populations have been noted to use these services at a lower rate, raising concern for inequities in access. [4][5][6] For example, a prior study in ophthalmology noted patients who identified as male, Black, non-English speaking, older, or with an education level of high school or less were less likely to receive telemedicine care.…”
Section: Introductionmentioning
confidence: 99%
“…In most of these studies, part of the telemedicine services was reimbursed by various insurances. In more than half of the studies, Medicare insurance was used to reimburse telemedicine services (4,16,22,23,25,26,27,29,30,35,36,(38)(39)(40)(41)(42)46). Medicare is funded by the government and regulated at the federal level (47).…”
Section: Discussionmentioning
confidence: 99%
“…In 18 studies (4,16,22,24,25,26,29,30,32,33,35,38,39,42,43,44,45,46) various insurances did not differentiate between the reimbursement of telemedicine services and face-to-face (traditional) visits. Also, among the studies related to the reimbursement of telemedicine services by private insurances (n = 13), only in 4 studies the rate of reimbursement of private insurances for telemedicine services was higher compared with other insurances (38,39,43,46).…”
Section: Reimbursement Methods Telemedicine Services and Classificati...mentioning
confidence: 98%